Construction and Index Analysis of Whole Chain Linkage Talent Training System Based on Fuzzy AHP Model. (6th July 2022) - Yi, Liu; Yan, Sun
Abstract : The construction and analysis of the entire chain linkage talent training system can measure the level of education and at the same time improve talents and drive development for the society. This paper uses the AHP model and CPII model to analyze the construction and index analysis of the entire chain linkage talent training system. The research shows that the weight value of personality literacy is the largest, followed by innovation literacy, emotional intelligence literacy, leadership and management ability literacy, and scientific literacy; in the analysis of the importance of the first-level indicators, it is found that most people think that personality literacy is the most important; in the consistency test of the first-level indicators, it shows that the results have good consistency; in the comment set of the second-level indicators, the highest comment value is expertise, independence and practicality, and diligence. Through the evaluation of the talent training system and its operation quality, it can provide reform ideas for education and management departments and can fully play the role of talents, create a good working atmosphere, and create suitable ways to improve capabilities. Through AHP's research on the construction of the entire chain linkage talent training system and indicators, it is found that the personality literacy has the largest weight value among the five first-level indicators. The cultivation of leadership, management ability, scientific literacy, etc. can better reflect the characteristics of talents.